Dampak Perkembangan Teknologi di Lingkungan Kampus - Uskono, Margaretha; Amaral, Pascoela Elsanty Pires; Mbara, Agnes Febiola Bale; Manek, Maria Stefania; Watu, Fransiskus Xaverius; Seran, Yohanes Maria Vianey Arin; Kota, Kornelius Juan Sebastian; Wasi, Yakobus Stefano Sutan Ria; Lian, Yohanes Pemandi (Universitas Pahlawan Tuanku Tambusai, 2024)
The development of technology has significantly influenced various aspects of campus life. This article examines the positive and negative impacts of technology in the context of higher education. By analyzing the transformation of learning, campus administration, and technological infrastructure, we explore how technology affects students' learning experiences and campus operational efficiency. Through this study, we highlight the importance of sustainable and continuous technology integration on campus to enhance academic experiences and support future innovations.